The Role of Digital Skills and Work-Life Balance in Shaping Labor Productivity in Manufacturing - Sania Sania; Adi Maryadi (DEAL: International Journal of Economics and Business, 2025)
This study aims to analyze the influence of digital skills development and work-life balance programs on labor productivity in Indonesia's manufacturing industry. In the context of global competition, Indonesia's labor productivity is still lagging behind compared to other ASEAN countries. Data shows that in 2022, Indonesia's labor productivity increased by 4.2%, but it is still below Malaysia and Singapore. This study uses a quantitative approach with SmartPLS 4.0 and involves a sample of 141 respondents from the manufacturing sector. This research emphasizes the importance of collaboration between governments, the private sector, and educational institutions in improving skills and technology adoption. Providing relevant training programs and incentives for companies to invest in technology and human resources is key to improving productivity. Through an integrated approach, it is hoped that labor productivity in the manufacturing sector can increase significantly and sustainably.